Global mapping of miRNA-target interactions in cattle (Bos taurus) - Troels K. H. Scheel (Nature Portfolio, 2017)
Abstract With roles in development, cell proliferation and disease, micro-RNA (miRNA) biology is of great importance and a potential therapeutic target. Here we used cross-linking immunoprecipitation (CLIP) and ligation of miRNA-target chimeras on the Argonaute (AGO) protein to globally map miRNA interactions in the cow. The interactome is the deepest reported to date. miRNA targeting principles are consistent with observations in other species, but with expanded pairing rules. Experimental mapping robustly predicted functional miR-17 regulatory sites. From miRNA-specific targeting for >5000 mRNAs we determined gene ontologies (GO). This confirmed repression of genes important for embryonic development and cell cycle progress by the let-7 family, and repression of those involved in cell cycle arrest by the miR-17 family, but also suggested a number of unappreciated miRNA functions. Our results provide a significant resource for understanding of bovine and species-conserved miRNA regulation, and demonstrate the power of experimental methods for establishing comprehensive interaction maps.